The role of microRNAs in axon regeneration after peripheral nerve injury: a bibliometric analysis - Shoukeer, Kutiluke; Aierxiding, Shalayiding; Aisaiti, Aikebaierjiang; Haibier, Abuduwupuer; Liu, Chunhua; Jia, Zhiwei; Aili, Abudunaibi; Shu, Li; Jiang, Kan; Muheremu, Aikeremujiang (Frontiers in Neurology, 2024)
Objective This study analyzed the current research hotspots and future development trends of the therapeutic effects of microRNA on PNI axonal regeneration through bibliometric methods. Moreover, the current advantages and disadvantages of this field as well as future development prospects are discussed in depth. Methods CiteSpace V and VOSviewer were used as bibliometric tools to complete the analysis of the research focus and direction of the published articles. To supplement, sort out, and summarize, we analyzed the research status of the study on the application of microRNAs for axonal regeneration after peripheral nerve injury from 2013 to 2023. Results A total of 207 publications were retrieved from the Web of Science database. After exclusion and screening, a final selection of 174 articles that met the research criteria. These 174 articles were authored by a total of 846 individuals, representing 24 countries and 199 institutions. Additionally, this study presents information on the annual publication output, country distribution, top 5 contributing authors, top 5 most cited articles, and top 10 contributing institutions. Conclusion As one of the hottest topics today, microRNAs have become the current research hotspot in neural inflammation, neural cell repair and regeneration, neural protection, and functional recovery. With more investment in research in this field, more high-quality articles will be published in both domestic and international outstanding journals, which will bring a new era for the treatment of peripheral nerve injury.